Experimental and numerical investigation of open-cycle miniature Joule-Thomson cryocooler for working temperatures 100 K to 150 K with single component coolants. (October 2022) - Shapiro, Alexander; Greenberg, Mordechai; Parahovnik, Anatoly
Highlights: Krypton and R14 were identified as potential coolants for HOT Joule-Thomson cryocooler. An open loop cryocooling setup was assembled to test and compare between the coolants. Despite higher isothermal effect of R14, krypton presented favorable cooling results. Krypton's compressibility and higher mass flux were the cause for its performance. Abstract: Krypton and R14 (i.e. single component gasses) were studied as potential coolants for an open cycle miniature Joule-Thomson cryocooler. Cooling experiments were performed at ambient temperatures of 293 K and 343 K followed by theoretical analysis and parameter decomposition. The theoretical analysis identified the isothermal effect, heat exchanger efficiency, and the mass flow rate as the governing parameters for cooling performance. A detailed analysis indicated that the effective cooling power of the cryocooler was influenced mostly by the mass flow rate. As a result, krypton had a Cool Down Time shorter by 27% and Cooling Duration Period longer by 8%, compared to R14.